2015
DOI: 10.1186/s40623-015-0376-y
|View full text |Cite
|
Sign up to set email alerts
|

Descent of tremor source locations before the 2014 phreatic eruption of Ontake volcano, Japan

Abstract: On 27 September 2014, Ontake volcano, in central Japan, suddenly erupted without precursory activity. We estimated and tracked the source locations of volcanic tremor associated with the eruption at high temporal resolution, using a method based on the spatial distribution of tremor amplitudes. Although the tremor source locations were not well constrained in depth, their epicenters were well located beneath the erupted crater and the summit. Tremor sources were seen to descend approximately 2 km over a period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…Ontake, rapid growth of tremor activity (Fig. 3 of Ogiso et al 2015) and tilting (Fig. 7 of Takagi and Onizawa 2016) were observed about 7 min before the eruption.…”
Section: Suggestions For Future Disaster Mitigationmentioning
confidence: 99%
See 2 more Smart Citations
“…Ontake, rapid growth of tremor activity (Fig. 3 of Ogiso et al 2015) and tilting (Fig. 7 of Takagi and Onizawa 2016) were observed about 7 min before the eruption.…”
Section: Suggestions For Future Disaster Mitigationmentioning
confidence: 99%
“…Maeda et al (2015) infer crack opening immediately before the eruption. Ogiso et al (2015) track the source location of tremor beneath the crater. Finally, Terakawa et al (2016) reveal stress changes associated with the eruption, strongly implying fluid-pressure changes.…”
Section: Seismological Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Miyagi et al (2014) reported that the volcanic ash consists exclusively of hydrothermally altered minerals with minor primary igneous particles. Some geophysical studies have reported analyses on seismicity linked to the eruption, investigating pre-and post-eruptive processes (e.g., Kato et al 2015;Maeda et al 2015;Ogiso et al 2015).…”
Section: The 2014 Eruptionmentioning
confidence: 99%
“…The toll of dead and missing was 63 (e.g., Cyranoski 2014). The seismic activities including tremors linked to the 2014 eruption have been deeply analyzed Maeda et al 2015;Ogiso et al 2015).…”
Section: Introductionmentioning
confidence: 99%